A Safe and Effective Magnetic Labeling Protocol for MRI-Based Tracking of Human Adult Neural Stem Cells - Stroh, Albrecht; Kressel, Jenny; Coras, Roland; Dreyer, Antje Y.; Fröhlich, Wenke; Förschler, Annette; Lobsien, Donald; Blümcke, Ingmar; Zoubaa, Saida; Schlegel, Jürgen; Zimmer, Claus; Boltze, Johannes (Frontiers in Neuroscience, 2019)
Abstract Magnetic resonance imaging provides a unique tool for in vivo visualization and tracking of stem cells in the brain. This is of particular importance when assessing safety of experimental cell treatments in the preclinical or clinical setup. Yet, specific imaging requires an efficient and non-perturbing cellular magnetic labeling which precludes adverse effects of the tag, e.g. the impact of iron-oxide-nanoparticles on the critical differentiation and integration processes of the respective stem cell population investigated. In this study we investigated the effects of very small superparamagnetic iron oxide particle (VSOP) labeling on viability, stemness and neuronal differentiation potential of primary human adult neural stem cells (haNSCs). Cytoplasmic VSOP incorporation massively reduced the transverse relaxation time T2, an important parameter determining MR contrast. Cells retained cytoplasmic label for at least a month, indicating stable incorporation, a necessity for long-term imaging. Using a clinical 3T MRI, 1x103 haNSCs were visualized upon injection in a gel phantom, but detection limit was much lower (5x104 cells) in layer phantoms and using an imaging protocol feasible in a clinical scenario. Transcriptional analysis and fluorescence immunocytochemistry did not reveal a detrimental impact of VSOP labeling on important parameters of cellular physiology with cellular viability, stemness and neuronal differentiation potential remaining unaffected. This represents a pivotal prerequisite with respect to clinical application of this method.